2004
DOI: 10.1095/biolreprod.103.018689
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cyclooxygenase-2 and Granulocyte-Macrophage Colony-Stimulating Factor in the Endometrial Epithelium of the Cow Is Up-Regulated During Early Pregnancy and in Response to Intrauterine Infusions of Interferon-τ1

Abstract: On the basis of results obtained in vitro, we previously proposed a model in which signals from the conceptus, namely interferon-tau (IFN-tau) and prostaglandin E2, increase the expression of cyclooxygenase (COX)-2 or granulocyte-macrophage colony-stimulating factor (GM-CSF) in immune and nonimmune cells of the bovine endometrium. Two experiments were conducted to verify the validity of this hypothesis in vivo. In experiment 1, the in vivo expression of COX-2 and GM-CSF during early pregnancy was monitored. Ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 103 publications
2
72
1
Order By: Relevance
“…This is in contrast to observed IFNT effects described in vitro (Asselin et al 1997a, 1997c, Parent et al 2002, Emond et al 2004, Tithof et al 2007, Godkin et al 2008. In addition, the release of all PG examined is strikingly concomitant, making it likely that the general rather than the specific synthases account for the vast increase in PG.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…This is in contrast to observed IFNT effects described in vitro (Asselin et al 1997a, 1997c, Parent et al 2002, Emond et al 2004, Tithof et al 2007, Godkin et al 2008. In addition, the release of all PG examined is strikingly concomitant, making it likely that the general rather than the specific synthases account for the vast increase in PG.…”
Section: Discussioncontrasting
confidence: 66%
“…The general PG synthase PTGS2 is not inhibited due to the presence of an embryo, instead there is an inconsistent evidence of the effect of IFNT on the expression of the general PG synthase PTGS2, showing either stimulative or no effects , Arosh et al 2004b, Emond et al 2004. While PGF 2a has primarily been ascribed to conduct luteolytic effects, elevated PGE 2 is associated with beneficial actions on uterine receptivity during the establishment of pregnancy (Arosh et al 2004b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no correlation was evident between PGHS2 mRNA levels in the endometrium of gravid horns and post-ovulatory progesterone concentrations. Some researchers report that recombinant IFNT increases PGHS2 expression in ruminant endometrial cells in vivo and in vitro (Asselin et al 1997;Arosh et al 2004;Emond et al 2004;Gray et al 2006), whereas others have reported a decrease (Chen et al 2006) or no effect (Kim et al 2003). Overall, the expression of PGHS2 in uteri with large compared with small conceptuses was greater, implying an effect of IFNT on its regulation; however, as the maximum expression was not in SR gravid horns with large conceptuses (those with the greatest exposure to IFNT), the relationship is inconsistent.…”
Section: Evaluation Of the Bovine Uterine Environmentmentioning
confidence: 98%
“…Granulocyte-macrophage colony-stimulating factor (GM-CSF), known to promote survival and growth of embryos, is expressed by the ruminant endometrium during early pregnancy and in response to intrauterine infusions of IFNτ (Teixeira et al, 1997;Emond et al, 2004). Separate culture of endometrial epithelial and stromal cells showed that high basal production of GM-CSF by epithelial cells is not regulated by recombinant ovine IFNτ.…”
Section: Maternal Recognition Of Pregnancy and The Pivotal Role Of Ifmentioning
confidence: 99%